Rancang bangun mesin pelurus poros dengan sistem rotasi - Enni Sulfiana; Ariyanto (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2023)
Indonesia is an industrial country that uses a lot of shafts as one of the important components in the production process. The shaft is one part of the rotating machine element whose function is to transmit power from one place to another. Shaft damage is one of the problems that often occurs, especially in the maintenance process that is not carried out according to factory standards or is not orderly in carrying out engine maintenance. The process of changing the shaft is expensive and the new material is sometimes not up to factory standards. Moving on from these problems, the author will design a shaft straightening machine with a rotation system. Previous research conducted by Juan Zhou designed a hexagonal axis straightening machine, but the hexagonal model still has a number of errors in its operation. The shaft straightening machine with the rotation method is expected to minimize errors and improve the shaft with better physical and mechanical properties after going through the heat treatment process with a rotation system